2017
DOI: 10.3389/fmicb.2017.01988
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Saccharomyces cerevisiae on a Wine Yeast Consortium in Natural and Inoculated Fermentations

Abstract: Natural, also referred to as spontaneous wine fermentations, are carried out by the native microbiota of the grape juice, without inoculation of selected, industrially produced yeast or bacterial strains. Such fermentations are commonly initiated by non-Saccharomyces yeast species that numerically dominate the must. Community composition and numerical dominance of species vary significantly between individual musts, but Saccharomyces cerevisiae will in most cases dominate the late stages of the fermentation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 84 publications
(124 reference statements)
2
44
0
Order By: Relevance
“…Interestingly, in the absence of S. cerevisiae, W. anomalus suppressed the rest of non-Saccharomyces species suggesting that the yeast can survive in the early stages of the fermentation better than the other yeast species and may utilize the nitrogen released by dead cells. However, in the presence of S. cerevisiae, W. anomalus specifically declined early in fermentation, suggesting an antagonistic interaction between both yeasts [30]. This interaction has also been proposed in apple cider fermentations [31].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 54%
See 1 more Smart Citation
“…Interestingly, in the absence of S. cerevisiae, W. anomalus suppressed the rest of non-Saccharomyces species suggesting that the yeast can survive in the early stages of the fermentation better than the other yeast species and may utilize the nitrogen released by dead cells. However, in the presence of S. cerevisiae, W. anomalus specifically declined early in fermentation, suggesting an antagonistic interaction between both yeasts [30]. This interaction has also been proposed in apple cider fermentations [31].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 54%
“…Yeast isolations from Malvar grape musts pointed out W. anomalus as one of the most frequent non-Saccharomyces species, and in addition, the yeast was a good producer of extracellular enzymes which may be beneficial in winemaking [29]. Recently, the dynamics of several non-Saccharomyces species were evaluated in synthetic must in the presence or absence of S. cerevisiae [30]. The study showed that the behaviour of the non-Saccharomyces species was differentially influenced by the presence of S. cerevisiae.…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 99%
“…The strive for more volatile aromas has spurred the search for alternative yeasts and renewed the interest in spontaneous fermentations [26]. Yet, due to the unpredictable and inconsistent outcomes of spontaneous fermentations, the development of improved starter cultures or consortia may provide better alternatives [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of New Zealand vineyards also began in the early 1800s. Domesticated allopolyploid S. cerevisiae of course plays a central role in wine making too, dominating the initial (Mangado et al 2018) and late (Bagheri et al 2017) stages of fermentation due to its high sugar processing rates and ethanol tolerance. Recent evidence suggests that S. cerevisiae not only dominates this ecosystem, but also directly influences the other constituent species (Bagheri et al 2017).…”
Section: Allopolyploidisation Pre-introductionmentioning
confidence: 99%
“…Domesticated allopolyploid S. cerevisiae of course plays a central role in wine making too, dominating the initial (Mangado et al 2018) and late (Bagheri et al 2017) stages of fermentation due to its high sugar processing rates and ethanol tolerance. Recent evidence suggests that S. cerevisiae not only dominates this ecosystem, but also directly influences the other constituent species (Bagheri et al 2017). Seemingly in parallel with the allopolyploidy observed in brewing yeasts, strains of Dekkera bruxellensis, a prominent industrial wine fermentation contaminant, also appear to be allopolyploids (Borneman et al 2014).…”
Section: Allopolyploidisation Pre-introductionmentioning
confidence: 99%